Blake, Modernity and Popular Culture
X, 240 p.
Keywords: This book explores the ways in which Blake reacted to the subcultures of his day, as well as how he has inspired popular, modernist and postmodernist figures until the present day. Blake's influence on later generations of writers and artists is more important than ever, extending into film, psychology, children's literature and graphic novels.